2001
DOI: 10.2134/jeq2001.301147x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Microbial Carbon and the Resource Quality of Soil Carbon

Abstract: The biological health of soil is an important aspect of soil quality because of the many critical functions performed by organisms in soil. Various indicators of soil quality have been proposed, but measurements of microbial biomass are most commonly used. During decomposition of plant residues in soil the relative intensities of the O-alkyl-C signal decreases and the alkyl-C signal increases in nuclear magnetic resonance (NMR) spectra. This leads to the suggestion that the alkyl-C to O-alkyl-C ratio of a soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…This index has been proposed as an indicator of the capacity for decomposition of OM (Baldock et al, 1997;de Nobili et al, 2008) and also as a sensitive indicator of humification during the early stages of leaf material decomposition (Almendros et al, 2000). A high ratio indicates a highly decomposed OM, which consequently is more resistant to rapid C loss (Webster et al, 2001). In our study, soil HA and FA from both compostamended soils (CSS and CMW) showed higher alkyl C/0-alkyl C ratios than those of the SS-and MSW-amended soils after the 1-yr incubation, meaning that the humic fraction formed in compost-amended soils was more stable.…”
Section: Cpmas Carbon-13 Nmr Characterization Of Humic Acid and Fulvimentioning
confidence: 99%
“…This index has been proposed as an indicator of the capacity for decomposition of OM (Baldock et al, 1997;de Nobili et al, 2008) and also as a sensitive indicator of humification during the early stages of leaf material decomposition (Almendros et al, 2000). A high ratio indicates a highly decomposed OM, which consequently is more resistant to rapid C loss (Webster et al, 2001). In our study, soil HA and FA from both compostamended soils (CSS and CMW) showed higher alkyl C/0-alkyl C ratios than those of the SS-and MSW-amended soils after the 1-yr incubation, meaning that the humic fraction formed in compost-amended soils was more stable.…”
Section: Cpmas Carbon-13 Nmr Characterization Of Humic Acid and Fulvimentioning
confidence: 99%
“…The presence of species such as lignin/tannin tend to slow down the decomposition process of litter considerably and are reported to be the most recalcitrant materials among the naturally occurring organic compounds (Hammel 1997). Webster et al (2001) and Hopkins et al (2000) reported that as ratio of alkyl-C to O-alkyl-C increases the resource quality as a substrate for heterotrophic microorganisms declines. The C species comprising polysaccharide C or carbohydrate C was invariably the largest group present in all the five litter species studied represented by the high peaks in the shift region 45-90 ppm (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Though many biological indicators of soil quality have been proposed (Elliot et al 1996;Pankhurst et al 1997), microbial biomass measurement through substrate induced respiration method is often preferred as it can be applied to a range of soils and due to easiness in its measurement (Webster et al 2001).…”
mentioning
confidence: 99%
“…In contrast, a decrease was observed for the bound FA of both stubbed and woodland soil samples. The alkyl C to O -alkyl ratio has been suggested as an indicator of the decomposability of SOM (Baldock et al, 1997 ;Webster et al, 2001 ), high alkyl C to O -alkyl C ratios indicating a lower resource quality of SOM. All 13 C -NMR spectra of free FA display a strong signal in the O -alkyl C region and a lower proportion of N -alkyl and alkyl C than HA.…”
Section: Effects Of Reducing Carbon Inputs To Soilmentioning
confidence: 99%